Samuel Beckett and the visual arts - Carville, Conor, 1967- (Cambridge University Press, 2018)
This book outlines Beckett's passion for the visual arts as he developed his signature style between the 1930s and 1970s.
Keywords: Beckett, Samuel, -- 1906-1989 -- Knowledge -- Art.; Beckett, Samuel, -- 1906-1989; Art and literature -- Ireland -- History -- 20th century.; Arts, Modern -- 20th century.; Arts, Modern.; Art et littérature -- Irlande -- Histoire -- 20e siècle.; Arts -- 20e siècle.; LITERARY CRITICISM -- European -- French.; Art; Art and literature; Arts, Modern; Ireland; 1900-1999; History